Multidisciplinarity in Mechatronics (Docentes 2.0 Journal, 2019)
Multidisciplinarity is a non-integrative mix of several disciplines in which each one retains its methods and assumptions without change or development of other disciplines in the multidisciplinary relationship. In a multidisciplinary relationship, disciplines cooperate in a “mutual and cumulative but not interactive way. "Mechatronics is the multidisciplinary study that proposes the control of physical systems, through computational intelligence."
Keywords: Multidisciplinarity; Mechatronics